Rural-urban inequality in Africa: A panel study of the effects of trade liberalization and financial deepening - Mina Baliamoune-Lutz; Stefan H. Lutz (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
Using panel data from 39 countries, this paper examines the effects of financial deepening and openness to trade and foreign capital (FDI) on rural-urban inequality in Africa. Four estimations were performed–OLS pooled cross-section, GLS pooled cross-section, fixedeffects model and an adjusted fixed-effects specification with regional dummy terms. We have developed an alternative measure of rural-urban inequality, namely the ratio of growth in agricultural output to growth of manufacturing output. Overall, the econometric results show that openness to trade seems to contribute to reducing rural-urban inequality. However, the empirical evidence does not unambiguously delineate the nature of the impact FDI and financial deepening have on the rural-urban gap. The findings imply that there may be some support for the so-called offsetting-trend in inequality (OTI) hypothesis.
Keywords: 330